The stagnation-point flow and heat transfer of nanofluid over a shrinking surface in magnetic field and thermal radiation with slip effects : a stability analysis - Nurul Syuhada, Ismail; Norihan, Md Arifin; Roslinda, Nazar; Norfifah, Bachok (2017)
A numerical study is performed to evaluate the problem of stagnation – point flow and heat transfer towards a shrinking sheet with magnetic field and thermal radiation in nanofluid. The Buongiorno's nanofluid model is used in this study along with slip effect at boundary condition. By using non-similar transformation, the governing equations are able to be reduced into an ordinary differential equation. Then, the ordinary differential equation can be solved by using the bvp4c solver in Matlab. A linear stability analysis shows that only one solution is linearly stable otherwise is unstable. Based on the numerical results obtained, the dual solutions do exist at certain ranges in this study. Then, the stability analysis is carried out to determine which one is stable between both of the solutions.